Test of the activity of 96% ethanol extract gel of avocado seeds (Persea americana mill.) on burn wound healing in the back of new zealand rabbits - Ulya, Fajar Putri Nuril; Sari, Gigih Kenanga; Saraswati, Maulita (Journal of Health Management and Pharmacy Exploration, 2025)
Avocado seeds contain secondary metabolite compounds in the form of alkaloids, flavonoids, saponins, tannins, triterpenoids and steroids. The mechanism of flavonoids in inhibiting the inflammatory process in burns is through various methods, namely inhibiting capillary permeability, inhibiting the release of serotonin and histamine to the site of inflammation. In this study, avocado seed extract was obtained by maceration method and formulated into a gel preparation with a concentration of 5%, 10% and 15%. The gel base was used as a negative control, and the gel containing 10% placenta extract and 0.5% neomycin sulfate was used as a positive control, applied to burn wounds on the backs of New Zealand rabbits with a diameter of 2 cm. The activity test of avocado seed extract gel was conducted on 3 rabbits, with each formulation applied 3 times, and the wound diameter was measured daily. This test was conducted for ten days. Avocado seeds (Persea americana Mill.) contain alkaloids, flavonoids, tannins, saponins and titerpenoids. The results of observations of the healing and drying process of burns, avocado seed extract gel (Persea americana Mill.) on the 10th day were F1 (5%) wound diameter 0.2 cm, F2 (10%) wound diameter 0.1 cm, F3 (15%) wound diameter 0 cm. Avocado seed extract gel (Persea americana Mill.) with a concentration of 15% can provide the best effect on healing burns.